2005
DOI: 10.2135/cropsci2004.0334
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Acid‐PAGE Gliadin Pattern of Indian Wheats (Triticum aestivum L.) Representing Different Environments and Periods

Abstract: nomic traits, and environmental adaptation (Metakovsky and Branlard, 1998). Acid-PAGE analysis of gliadins from 159 Indian wheat (Triticum Because of their importance, the genetic polymoraestivum L.) cultivars developed during the last five decades was accomplished to identify gliadin band patterns as well as the extent phism of gliadins has been used to evaluate genetic diof genetic diversity. Extensive polymorphism [genetic diversity index versity within several germplasms in Australia (Metakov-(H ) ϭ 0.875]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In other studies, Zaefizadeh et al (2010) reported 66 polymorphic bands and 81 patterns in durum wheat landraces and Ojaghi & Akhundova, (2010) reported 48 bands and 47 patterns in double haploid T. aestivum. When comparing the different gliadin regions, α-gliadin region showed the lowest number of band patterns which is similar to find- ings in studies on other wheat species (Ram et al, 2005;Aliyeva et al, 2012).…”
Section: Gliadin Electrophoretic Patternssupporting
confidence: 86%
“…In other studies, Zaefizadeh et al (2010) reported 66 polymorphic bands and 81 patterns in durum wheat landraces and Ojaghi & Akhundova, (2010) reported 48 bands and 47 patterns in double haploid T. aestivum. When comparing the different gliadin regions, α-gliadin region showed the lowest number of band patterns which is similar to find- ings in studies on other wheat species (Ram et al, 2005;Aliyeva et al, 2012).…”
Section: Gliadin Electrophoretic Patternssupporting
confidence: 86%
“…Four from 25 wheat cultivars carried Gli-D1a allele, 13 cultivars b allele, 3f allele, one g allele and 4 cultivars k allele. In numerous studies reported that each allele of gliadins has specific connection to biological traits of wheat and could use as a markers for some quality traits (METAKOVSKY et al, 1997;MENKOVSKA et al, 2002), agronomic traits and environmental adaptation (METAKOVSKY and BRANLARD, 1998;RAM et al, 2005). Genetic polymorphism of gliadins has been studied in different Countries, because of cultivar identification.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent allele should have some definite value, since it has succeeded in competition with many other alleles during the breeding process. It could be evaluate that this allele is linked to genes influencing agronomical important traits in certain environmental conditions (LAGRAIN et al, 2005;RAM et al, 2005). The value of frequent alleles my be in their contribution to a higher plant adaptability.…”
Section: Gli-d1 Allelesmentioning
confidence: 99%
“…Gliadins have been used by researchers around the world for genetic diversity studies in wheat, and large numbers of bands have been reported (Labuschagne et al 2000, Tanaka et al 2003, Ram et al 2005. The nomenclatures used in these studies are all based either on the procedure suggested by Metakovsky (1991) or on gliadin mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of different gliadin alleles make it possible to distinguish wheat genotypes. Gliadins were commonly used in cultivar diversity studies in many countries, such as Australia (Metakovsky et al 1990), Yugoslavia , Italy (Metakovsky et al 1994), France (Metakovsky andBranlard 1998, Branlard et al 2003), Portugal (Igrejas et al 1999), South Africa (Labuschagne et al 2000), Russia (Romanova et al 2001), Japan (Tanaka et al 2003) and India (Ram et al 2005). Furthermore, the gliadin Gli-1 loci are tightly linked to Glu-3 and the specific alleles at the two groups of loci may be closely associated.…”
mentioning
confidence: 99%